2022
DOI: 10.3389/fimmu.2022.864817
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Alcohol Use Disorder on Tuberculosis: A Review of the Epidemiology and Potential Immunologic Mechanisms

Abstract: Globally, an estimated 107 million people have an alcohol use disorder (AUD) leading to 2.8 million premature deaths each year. Tuberculosis (TB) is one of the leading causes of death globally and over 8% of global TB cases are estimated to be attributable to AUD. Social determinants of health such as poverty and undernutrition are often shared among those with AUD and TB and could explain the epidemiologic association between them. However, recent studies suggest that these shared risk factors do not fully ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 152 publications
0
6
0
Order By: Relevance
“…These associations can be attributed to a combination of various factors. Firstly, individuals struggling with alcoholism or drug addiction may experience compromised immune systems, making them more susceptible to TB infection and hindering their ability to effectively combat the disease ( 32 ). Secondly, the increased risk of reinfection among this vulnerable population further complicates their treatment outcomes ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…These associations can be attributed to a combination of various factors. Firstly, individuals struggling with alcoholism or drug addiction may experience compromised immune systems, making them more susceptible to TB infection and hindering their ability to effectively combat the disease ( 32 ). Secondly, the increased risk of reinfection among this vulnerable population further complicates their treatment outcomes ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…Except for one study among multi-drug resistant TB patients from South Africa, the prevalence of alcohol use disorder among persons with TB in our study was much higher than prior prevalence estimates among TB patients in sub-Saharan Africa. 26 Alcohol use has a doseresponse relationship with TB, where larger consumption amounts -likely through several mechanisms 27 -is associated with an increasing risk of both developing [28][29][30] and dying from TB. 29,31 Smoking is also an important risk factor for developing TB, 32,33 and combined with alcohol use, may portend to an even higher TB risk through a synergistic relationship.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a study conducted in Eastern Europe reported a median survival time of 5.9 years following diagnosis with MDR-TB or XDR-TB, which decreases to 1.9 years for patients also diagnosed with HIV (8). Additional risk factors for death among TB patients include alcoholism, male gender and old age, among others (7,9).…”
Section: Introductionmentioning
confidence: 99%